Giant Pulmonary Artery Aneurysm in a Patient with Rheumatic Mitral Stenosis - Singh, Vikas (Heart Views, 2014)
Pulmonary artery (PA) aneurysm is a rare condition, frequently associated with pulmonary hypertension. However, the evolution and treatment of this pathology is still not clear. We report a case of a 45-year-old female patient with giant PA aneurysm associated with rheumatic mitral stenosis and severe pulmonary arterial hypertension. The patient had undergone balloon mitral valvotomy around 7 years back; aneurysm was first identified 3 years back during routine follow-up. The PA aneurysm size, however, had remained almost unchanged with associated severe pulmonary regurgitation. Surgical correction was advised but denied by the patient. To our knowledge, this is the first case report of such a large PA aneurysm in association with rheumatic heart disease. Although medical therapy for pulmonary hypertension was started, surgical correction of the aneurysm was advised in order to prevent the future complications.